2020
DOI: 10.18517/ijaseit.10.3.10973
|View full text |Cite
|
Sign up to set email alerts
|

Land Flooding Effect Before and After Planting on Rice Yield in the System of Rice Intensification

Abstract: Rice is the primary carbohydrate source for half world population, particularly for Asian people, and rice demand also increases for non-Asian people. Rice provides the bulk daily calories for humans and animals. One of the problems in SRI method is weed. Many efforts to control weed in the SRI method and one of the way island flooding before planting. The objective of the research was to study the land flooding effect before planting in controlling weed to yield components of several rice varieties. The resea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 30 publications
0
0
0
Order By: Relevance
“…The increasing demand for rice is currently not comparable to rice production per hectare and the conversion of agricultural land to nonagricultural is the main cause of low national rice production. Rice is the main source of carbohydrates for half of the world's population, especially for Asians, and rice demand is rising for non-Asians as well [3]. The findings demonstrated that land acreage, urea fertilizer, and NPK fertilizer all had an impact on corporate farming's ability to produce rice [4].…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…The increasing demand for rice is currently not comparable to rice production per hectare and the conversion of agricultural land to nonagricultural is the main cause of low national rice production. Rice is the main source of carbohydrates for half of the world's population, especially for Asians, and rice demand is rising for non-Asians as well [3]. The findings demonstrated that land acreage, urea fertilizer, and NPK fertilizer all had an impact on corporate farming's ability to produce rice [4].…”
Section: Introductionmentioning
confidence: 98%
“…When SRI farming is done in tidal areas, there are two significant issues, including the presence of Fe, which may be hazardous to plants, and a lack of nutrients [12]. Rice is a major source of daily calories for both people and animals [3]. By reducing inter-plant competition, transplanting young, single seedlings at a wide spacing, enhancing favorable soil conditions with organic amendments, increasing soil aeration through weeding, and using controlled water management, the system of rice intensification (SRI) aims to create the best conditions for healthy plant growth [13].…”
Section: Introductionmentioning
confidence: 99%
“…The duration of solar radiation, air temperature, and wind speed also positively affect potential evapotranspiration, while relative humidity negatively affects potential evapotranspiration [4]. Meanwhile, the factors that affect evaporation are temperature differences, irradiation time, wind speed, and rainfall [5] This evapotranspiration can be used to estimate crop water requirements. In the field of agricultural irrigation, evapotranspiration is divided into reference evapotranspiration (ETo) and crop evapotranspiration (ETc).…”
Section: Introductionmentioning
confidence: 99%